The constant reality beyond exception and rule in Dietrich Bonhoeffer's theology - K. Radler (Acta Theologica)
Due to the many warnings at the onset of the COVID-19 pandemic of an increased transfer of power to governments and the subsequent impending demise of democracy, this article presents a theological response to a persistent theory of autocratic power. Employing, but reinterpreting the semantics of the concepts of the jurist and theorist of state Carl Schmitt, the theologian Dietrich Bonhoeffer redirects the former’s rhetoric regarding history, rule, nothingness, creation ex nihilo and miracle. As a result, Bonhoeffer responds to a secular method with faith in Christ’s cross and provides for a reality that can serve as a constant grounding for a new life carried by ultimate hope.